Homopolymer and Copolymer of Dodecyl Acrylate Incorporated with Elsholtzia blanda–Chitosan-Mediated CuO Nanoparticles: A Study on Their Multifunctional Additive Performance in Lubricating Oils - Ahungshi, Leiyami; Maheo, Athisa Roselyn; Hoque, Mainul (Asian Journal of Chemistry, 2026)
Polymer nanocomposite has attracted a lot of attention since it outperforms traditional polymers in the lubricant industry. In this study, chitosan and the aqueous leaf extract of the fragrant medicinal plant Elsholtzia blanda were used to synthesise copper oxide nanoparticles. Several analytical methods, such as X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), high-resolution transmission electron microscopy (HRTEM) and selected area electron diffraction (SAED), were used to characterize the produced E. blanda-chitosan-mediated copper oxide nanoparticles (COEC). Several instrumental studies were used to describe the polymer/COEC nanocomposites that were created by incorporating these COEC nanoparticles at different concentrations into olive oil-based polymers. In accordance with normal ASTM methods, the nanocomposites were blended with mineral-based oil in varying amounts to evaluate their effectiveness as pour point depressants, viscosity index improvers and anti-wear additives. The results showed that adding more nanocomposite material greatly improved the formulated oil’s overall lubricating capabilities.